Occluded vein as a predictor for complications in non-infectious transvenous lead extraction. (19th May 2022) - Milman, A; Massalha, E; Jia, K; Meitus, A; Kariv, S; Shafir, Y; Glikson, M; Luria, D; Sabbag, A; Beinart, R; Nof, E; Leshem, E
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cardiovascular implantable electronic device (CIED) use is steadily increasing, with subsequent need to solve lead failure issues and device upgrades with an occluded vein. Transvenous lead extraction (TLE) has inherent risks that must be carefully weighed. Currently there is lack of conclusive data regarding many non-infectious indications. Methods: A retrospective study on indications and outcomes of TLE for non-infectious reasons at our medical center, between the years 2011 to 2020 was performed. Occluded vein (OV) presence was compared for characteristics, extraction methods and periprocedural complications and outcomes. Results: A total of 88 patients underwent TLE for non-infectious reasons. The majority were referred due to lead malfunction (70.5%) and CIED upgrade with an OV (25%), while 4 patients had other TLE indication (intractable pain, heart transplant, severe Tricuspid regurgitation, and irradiation). fourteen patients referred due to lead malfunction had an OV observed during venography. The OV group (36 patients) were significantly older (65.7±14.1 vs 53.8±15.9 respectively, p=0.001) and had more comorbidities. EF was significantly lower for the OV group (27.5% vs 57.5%, p=0.001) as was longer lead dwell time (3226±2324 vs 2191±1355 days, respectively, p=0.012). Major complications were exclusive for the OV group (16.7% vs none, p=0.02), and most minor complications occurred in the OV group as well (38.9% vs 4.1% respectively, p<0.001). Laser sheath and Mechanical tools for TLE were frequently used for OV as compared to the non-occluded group (94.4% vs 73.5% respectively, p=0.012). Procedure success was higher in the non-occluded group compared to the OV group (98% vs 83.3%, respectively, p=0.047). Despite these results, peri-procedural mortality was similar between groups. Conclusions: Among TLE for non-infectious reasons, vein occlusion appears as a major predictor for complex TLE tools use, complications, and procedural success. Venography should be routinely performed prior to non-infectious TLE to identify high-risk patients.